Model Komunikasi Pengembangan Masyarakat Berbasis Kampanye Digital Dalam Meningkatkan Literasi Kesehatan Tentang Konsumsi Gula Di Kota Bengkulu - Bayu Risdiyanto; Martha Heriniazwi Dianthi; Riski Defa Agung; Dwi Novriansyah (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
Excessive sugar consumption is a public health problem because it can increase the risk of non-communicable diseases, especially diabetes mellitus. In Bengkulu City, diabetes remains an important health issue, so health communication is needed not only to provide information but also to improve public health literacy and encourage healthier behavior. This study aims to formulate a community development communication model based on digital campaigns to improve health literacy about sugar consumption in Bengkulu City. This study uses a descriptive qualitative approach with content analysis of digital campaign materials published by the Bengkulu City Health Office, Bengkulu City Media Center, community health centers, and the Ministry of Health of the Republic of Indonesia. The results show that local digital campaigns mostly focus on health checks, screening, and healthy lifestyle messages. Meanwhile, national campaigns are stronger in explaining sugar consumption limits, diabetes risks, and education about sugar, salt, and fat. This study produces a communication model that integrates digital media, health messages, community health centers, Posbindu, health cadres, and community participation. This model places digital campaigns as a medium for awareness, education, empowerment, and behavior change in controlling sugar consumption.